For whose sake do couples relocate? Gender, career opportunities and couples' internal migration - Maria Brandén; Sara Ström (Institute for Labour Market Policy Evaluation (IFAU), 2011)
The aim with this study is to examine how career possibilities in the man's and the woman's occupations - in the country as a whole, as well as in the region where the couple resides - affect heterosexual couples' regional mobility. The context is Sweden - a country with a strong dual earner norm combined with a very sex segregated labor market. In the analyses we perform logistic regressions on Swedish register data, 1998-2007. We study how four dimensions of career possibilities affect couples' geographical mobility and are interested in if their effect varies by gender. The dimensions are geographical wage differences, current career, occupational level and wage compression in occupations. In summary, our findings indicate that male and female career opportunities affect the couple in different ways when one moves beyond focusing on the level of their occupations. In particular the effect from wage compression in occupations seems to be dependent on gender, with a clear effect for men and no effect for women. Even when including measures of career opportunities within professions, there exist some non-egalitarian patterns in whose career couples adjust to. It hence seems as if couples adapt somewhat more to the man's career possibilities than the woman's, even when we adjust for the underlying gender differences in career possibilities.
Keywords: R23; J16; 330; Regional mobility; internal migration; sex segregation; career; gender